Boosted Genomic Literacy in Nursing Students via Standardized-Patient Clinical Simulation: A Mixed-Methods Study. - Garcia-Gutiérrez, Daniel; Ramírez-Baraldes, Estel·la; Orera, Maria; Seidel, Verónica; Martínez, Carmen; García-Salido, Cristina (Nursing Reports, 2025)
Background: Genomic information is becoming integral to nursing practice, yet undergraduate curricula often provide limited opportunities to apply this knowledge in realistic settings. Objective: To evaluate the impact of a clinical simulation-based intervention on nursing students' learning of genetic counseling, with a focus on knowledge acquisition, communication skills, and student satisfaction. Methods: A sequential mixed-methods study was conducted with 30 third-year nursing students enrolled in the elective Genetics Applied to Health Sciences. Quantitative data comprised (i) pre-/post-simulation knowledge tests, (ii) a satisfaction questionnaire, and (iii) final course grades, which were compared with grades of a cohort from the previous academic year that had no simulation component (n = 28). Qualitative insights were gathered through field notes and semi-structured interviews with six purposively selected participants. During the intervention each student rotated through the roles of genetic-counseling nurse, patient, and observer, followed by a facilitated debriefing. Results: Post-simulation knowledge scores and final course grades were significantly higher than both baseline values and the historical comparison cohort. Students reported very high satisfaction, highlighting the authenticity of the scenarios and the usefulness of immediate feedback. Qualitative analysis showed that role rotation fostered deeper understanding of counseling complexities, improved empathic communication, and bolstered self-confidence when discussing hereditary risk. Conclusions: Embedding standardized-patient simulation into undergraduate genetics courses measurably improves students' knowledge, communication proficiency, and satisfaction. These findings support incorporating similar simulation-based learning activities to bridge the gap between theoretical genetics content and real-world nursing practice.